Самономінації в епістолярних текстах Тараса Шевченка - Богдан, Світлана; Bohdan, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті окреслено основні способи автопортретування, з’ясовано словесні засоби його експлікації в епістолярних текстах Тараса Шевченка, визначено й проаналізовано найчастотніші самономінації, що становлять центр його автопортретних ознак, проаналізовано їх стилістичну диференціацію і вплив прагматико-комунікативних чинників на їх появу та актуалізацію в певних епістолярних діалогах. Встановлено, що самономінації є не лише елементом автопортретування Тараса Шевченка, а й важливим способом самооцінки. The article installs the basic ways of autoportraiting and means of its verbal explication in Taras Shevchenko’s epistolary texts, presents and analyzes the most frequent self-nominations which become the center of self-portrait features, their stylistic differentiation and the influence of the pragmatic-communicative factors on their appearance and update certainly epistolary dialogues have been also studied. The usage of self-nominations substantially depends on the factor of addressee and the emotional health of addresser. Most significantly, this paper determines the choice of these tools and the relationship of the communicants. It was found that self-nominations are not only the elements of Taras Shevchenko’s autoportraiting, but also are an important way of self-esteem. The analysis of epistolary texts in the temporal dimension indicates the dynamics of some names and other functioning immutability. The source of insignificant part of these nominations are characteristics, given to Taras Hryhorovych by his friends, acquaintances, subsequently adopted / or, conversely, missed them both as real and inherent / or inherent.
Self-nominations in Taras Shevchenko’s epistolary texts
Keywords: автопортретування; епістолярний текст; самономінації; Тарас Шевченко; меліоративна і пейоративна оцінка; autoportraiting; epistolary text; self-nominations; Taras Shevchenko; mejorative and pejorative assessment